ANALISA FUNDAMENTAL EMITEN BANK MINI DI MASA PANDEMI - Christian Arman Lalang; Arwita Sari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Indonesia's economic growth during the pandemic season was marked by a changeof mindset and financial management from a saving society to an investmentsociety. During the pandemic, people prefer buying stocks as an alternative toincrease their income while working from home. However, in the selection of stockissuers, fundamental analysis needs to be carried out before choosing to buyshares. As research in the financial sector for the period 2019-June 2021,fundamental analysis and descriptions of Earning Per Share (EPS) and PriceEarning Ratio (PER) need to be known as a basis for consideration in makingstock investment decisions. This type of research is a descriptive method with asample of bank and similar sub-sector companies listed on the Indonesia StockExchange. The analysis technique used is fundamental analysis with EPS and PERapproaches. The research design is a time series design method with a researchperiod of 2 years and 6 months. Based on the results of fundamental analysis withthe EPS and PER approaches, it can effectively assist investors in assessingcompany shares in making stock investment decisions in the financial sub-sector.The difference in this study lies in the object of research, research time, measuringinstruments, literature used, theory used, and research results.